Above-Level Test Item Functioning Across Examinee Age Groups. (February 2016) - Warne, Russell T.; Doty, Kristine J.; Malbica, Anne Marie; Angeles, Victor R.; Innes, Scott; Hall, Jared; Masterson-Nixon, Kelli
Above-level testing (also called above-grade testing, out-of-level testing, and off-level testing ) is the practice of administering to a child a test that is designed for an examinee population that is older or in a more advanced grade. Above-level testing is frequently used to help educators design educational interventions for gifted children, especially those who may be candidates for grade skipping or Talent Search programs. However, little research has been conducted on how test items function when administered to a younger population, despite professional standards that require examiners to gather validity evidence when administering a test for a new population. In this article, we explain two studies in which we compared item functioning across two populations of examinees: gifted middle school students and older examinees that the tests were designed for. Results from Study 1 indicated a high correlation between item difficulty statistics for both groups on the Iowa Tests of Basic Skills. Results from Study 2—a mixed-methods study—showed that even though the two groups were similar in ability (as measured by the Reynolds Intellectual Assessment Scales), the high school students completed SAT-M test items more quickly and demonstrated more familiarity with the test content. In both studies, test items generally operate similarly for the two age groups. However, important local curriculum and individual educational history may cause some items to operate differently when administered above level.